Diffuse Facial Hyperpigmentation as a Presenting Sign of Lupus Erythematosus: Three Cases and Review of the Literature - Shir Azrielant; Eran Ellenbogen; Alon Peled; Valentina Zemser-Werner; Liat Samuelov; Eli Sprecher; Mor Pavlovsky (Karger Publishers, 2021)
Lupus erythematosus (LE) is an autoimmune disorder commonly affecting the skin; cutaneous lesions may indicate systemic involvement, warranting further evaluation. Photosensitivity, which may result in hyperpigmentation, is a well-known feature of the disease. In contrast, the prevalence of primary hyperpigmentation as a presenting sign of LE is not well established. Here, we compare 3 unique cases of diffuse facial hyperpigmentation as the primary manifestation of LE (cutaneous or systemic) and review previously reported cases. Our data highlight the need for considering LE in the differential diagnosis of facial hyperpigmentation and substantiate the importance of this unique lupus variant in early diagnosis and patient evaluation.